1999
DOI: 10.13031/2013.13332
|View full text |Cite
|
Sign up to set email alerts
|

Riparian Ecosystem Management Model (Remm): I. Testing of the Hydrologic Component for a Coastal Plain Riparian System

Abstract: R iparian ecosystems are known to be important in the control of nonpoint source pollution and maintenance of healthy aquatic ecosystems (Lowrance et al., 1997). The Riparian Ecosystem Management Model (REMM) (Lowrance et al., In press) has been developed as a tool to aid natural resource agencies and others in making decisions regarding management of riparian buffers to control nonpoint source pollution. REMM is also intended as a tool for researchers to study the complex dynamics of hydrology and water quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 9 publications
1
38
0
2
Order By: Relevance
“…Bryant et al (2005) reported an interception loss of 17.7% in the same watershed. For riparian forests located on coastal plain watersheds in Georgia, Inamdar et al (1999a) reported average annual interception loss of 15%. This discrepancy in interception losses between this study and reported literatures is not expected.…”
Section: Resultsmentioning
confidence: 99%
“…Bryant et al (2005) reported an interception loss of 17.7% in the same watershed. For riparian forests located on coastal plain watersheds in Georgia, Inamdar et al (1999a) reported average annual interception loss of 15%. This discrepancy in interception losses between this study and reported literatures is not expected.…”
Section: Resultsmentioning
confidence: 99%
“…This study was designed to provide information on both concentrations and loads of N, P, and chloride in direct surface runoff moving through a managed riparian buffer system. This is a companion study to previously published studies from the same site on sediment and water transport (Sheridan et al, 1999); subsurface hydrology (Bosch et al, 1994, 1996); herbicide transport (Lowrance et al, 1997); subsurface nutrient and chloride transport (Hubbard and Lowrance, 1997; Lowrance et al, 2000b); soil ecology (Lowrance, 1992; Ettema et al, 1999a, 1999b); and model testing (Inamdar et al, 1999a, 1999b; Lowrance et al, 2000a).…”
mentioning
confidence: 87%
“…In RibAV , the actual evapotranspiration ( E ) is determined by the soil saturation, the roots' connectivity with the water table (Maddock and Baird, ; Baird and Maddock, ; Maddock et al , ) and the soil moisture content (Inamdar et al ., ; Altier et al ., ; Dahm et al ., ). This is the reason why the actual evapotranspiration estimation in the RibAV model includes the evapotranspiration from the unsaturated upper part of the soil ( E u ) represented by the static storage and the evapotranspiration from the saturated zone of the soil ( E s ): Et=Eut+Est…”
Section: The Ribav Modelmentioning
confidence: 99%